2019
DOI: 10.3390/en12091718
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal-Based Carbon Sequestration by Converting LNG-Fired Waste CO2 into Red Gold Astaxanthin: The Potential Applicability

Abstract: The combinatorial approach of anthropogenic activities and CO2 sequestration is becoming a global research trend to alleviate the average global temperature. Although microalgae have been widely used to capture CO2 from industrial flue gas, the application of bioproducts was limited to bioenergy due to the controversy over the quality and safety of the products in the food and feed industry. Herein, the waste CO2 emitted from large point sources was directly captured using astaxanthin-hyperproducing microalgae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…However, higher biofixation capacities are reported at concentrations of approximately 10% CO 2 and have encouraged the development of strategies such as the intermittent injection of gas into the cultures or dilution of the gases, as reported by Yadav et al [183], Moheimani et al [169], and Matito-Martos et al [189]. Another strategy used to minimize the toxic effect of high concentrations of CO 2 (15.6%), and in this specific case, the presence of hydrogen sulfide gas (H 2 S) (120 ppm), is the use of scrubbers [187] and the serial connection of photobioreactors [187,190]. Recently, Chauhan et al [180] demonstrated that the pre-acclimatization of microalgae could improve biofixation performance in the presence of SOx and NOx.…”
Section: Microalgae Potential For Flue Gases Fixationmentioning
confidence: 99%
“…However, higher biofixation capacities are reported at concentrations of approximately 10% CO 2 and have encouraged the development of strategies such as the intermittent injection of gas into the cultures or dilution of the gases, as reported by Yadav et al [183], Moheimani et al [169], and Matito-Martos et al [189]. Another strategy used to minimize the toxic effect of high concentrations of CO 2 (15.6%), and in this specific case, the presence of hydrogen sulfide gas (H 2 S) (120 ppm), is the use of scrubbers [187] and the serial connection of photobioreactors [187,190]. Recently, Chauhan et al [180] demonstrated that the pre-acclimatization of microalgae could improve biofixation performance in the presence of SOx and NOx.…”
Section: Microalgae Potential For Flue Gases Fixationmentioning
confidence: 99%
“…These algae grow well in all types of aquatic environments, for example freshwater, marine, and hypersaline, also moist soils and rocks [ 35 ]. They are recognised for several potential applications such as functional food [ 16 , 36 , 37 ], animal feed [ 16 , 21 ], biomedicals [ 38 , 39 ], prebiotics [ 33 , 40 , 41 ], cosmetics [ 42 ], and organic manures [ 43 ], wastewater treatment [ 43 – 45 ] high value [ 46 ] and biofuel production [ 15 , 47 ]. Furthermore, several studies have addressed health benefits of such microalgal compounds comprising antioxidant, anti-inflammatory, antimicrobial, antiobesity, and anticancer properties, besides hypocholesterolemic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advantages, flue gas supplies can be temporarily interrupted at any time due to their dependence on equipment and machines that are prone to failure. To minimize the use of external energy, the outdoor cultivation of microalgae utilizing sunlight as the sole energy source requires a culture period of 1 to 4 weeks [47,48]. If the CO 2 injection is halted during the night (no light) the pH will not change considerably as compared to the daytime (light).…”
Section: Introductionmentioning
confidence: 99%
“…HEPES and Tris buffer systems are widely used to maintain stable pH in lab-scale photoautotrophic microalgal cultivation. However, the applications of large-scale culture systems are limited by to their high cost [48]. Accordingly, Choi et al developed an affordable bicarbonate buffer system applicable to large-scale microalgae processes by utilizing flue gas emitted from power plants [9].…”
Section: Introduction Of Urea and Kh 2 Po 4 To Microalgae Culture System For Preventing Cell Growth Inhibition From Interruption In Co 2 mentioning
confidence: 99%